A Qualitative Exploration of Service Users' Information Needs and Preferences When Receiving a Serious Mental Health Diagnosis - Milton, A.; Mullan, Barbara (Springer New York LLC, 2015)
Helpful strategies for communicating news of a serious mental health diagnosis are poorly understood. This study explored service users' preferences for how they would like clinicians to deliver such news when a diagnosis of mental illness is made. Qualitative interviews were conducted with forty-five individuals identifying with serious mental illness in eleven community based mental health facilities. Inductive thematic analysis resulted in eight primary themes. Five themes related to the structure and content of the discussion; including a focus on information exchange, using an individualized collaborative partnership paradigm, addressing stigma, balancing hope with realism, and recognizing the dynamic nature of diagnosis. The remaining themes related to the involvement of others; including the importance of clinicians' communication and relationship skills, involvement and education of carers, and offering an opportunity for peer support. The product of the synthesis of themes is a stepwise model for communicating news of mental health diagnosis.